2021
DOI: 10.3390/ijms222111422
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Extract from Purple Sweet Potato Exacerbate Mitophagy to Ameliorate Pyroptosis in Klebsiella pneumoniae Infection

Abstract: Given the rise of morbidity and mortality caused by Klebsiella pneumoniae (KP), the increasing number of strains resistant to antibiotics, and the emergence of hypervirulent Klebsiella pneumonia, treatment of KP infection becomes difficult; thus, novel drugs are necessary for treatment. Anthocyanins, or natural flavonoids, have an extensive effect against bacterial infection. However, few studies on anti-KP are identified. Here, we evaluated the therapeutic effect of purple sweet potato anthocyanins (PSPAs) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…In this study, dietary BA supplementation decreased the expression of the above nine immune-related DEGs and the corresponding signaling pathways. Anthocyanin regulated the innate immune system and reduced bacterial systemic dissemination in mice challenged with Klebsiella pneumoniae (Dong et al, 2021 ) and was used as a nutraceutical strategy to modulate stress and immune response in vertebrates (Khan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dietary BA supplementation decreased the expression of the above nine immune-related DEGs and the corresponding signaling pathways. Anthocyanin regulated the innate immune system and reduced bacterial systemic dissemination in mice challenged with Klebsiella pneumoniae (Dong et al, 2021 ) and was used as a nutraceutical strategy to modulate stress and immune response in vertebrates (Khan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al. reported that purple sweet potato anthocyanins (PSPAs) inhibited NLRP3 inflammasome activation by promoting parkin-dependent mitophagy and reducing the release of mtROS and mtDNA; this resulted in reduced lung inflammation and mortality of Klebsiella pneumoniae -infected mice ( 114 ). Suhuang exhibited a positive effect on mitochondrial homeostasis in ALI mice by reducing mtROS overproduction and mtDNA release, downregulating MMP9 expression, and inhibiting NF-κB and NLRP3 inflammasome activation ( 115 ).…”
Section: Organ-level Evaluation Of Trauma-related Sirs Induced By Mtd...mentioning
confidence: 99%
“…Mouse primary alveolar macrophages (AMs) were isolated as previously described (Dong et al, 2021). In brief, mice were killed, and the thoracic cavity and trachea were exposed.…”
Section: Primary Cells and Cell Linesmentioning
confidence: 99%